ONE OF THE MOST CRITICAL CONCERNS NOW IS THE TRANSITION TO A GREEN ECONOMY - Misirov Komoliddin Mamasabirovich (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This article focuses on the transition to a green economy, which is one of the issues confronting the world's governments in this era of globalization. The most serious challenges to the globe are environmental threats. Aspects connected to determining the best strategy to mitigate these environmental hazards in the country by transitioning to a green economy are underlined.